Tackle Epithelial-Mesenchymal Transition With Epigenetic Drugs in Cancer - Dong, Bo; Qiu, Zhaoping; Wu, Yadi (Frontiers in Pharmacology, 2020)
Epithelial-mesenchymal Transition (EMT) is a de-differentiation process in which epithelial cells lose their epithelial properties to acquire mesenchymal features. EMT is essential for embryogenesis and wound healing but is aberrantly activated in pathological conditions like fibrosis and cancer. Tumor-associated EMT contributes to cancer cell initiation, invasion, metastasis, drug resistance and recurrence. This dynamic and reversible event is governed by EMT-transcription factors (EMT-TFs) with epigenetic complexes. In this review, we discuss recent advances regarding the mechanisms that modulate EMT in the context of epigenetic regulation, with emphasis on epigenetic drugs, such as DNA demethylating reagents, inhibitors of histone modifiers and non-coding RNA medication. Therapeutic contributions that improve epigenetic regulation of EMT will translate the clinical manifestation as treating cancer progression more efficiently.